Advancements in the application of biomaterials in neural tissue engineering: A review - Iyad A Hammam; Ryan Winters; Zhongkui Hong (Biomedical Engineering Advances, 2024)
Tissue engineering approaches have revolutionized the treatment of neural nerve injuries caused by disruption to axonal route or tract. Neurodegenerative diseases, traumatic brain injury (TBI), spinal cord injury (SCI), and peripheral nerve injury (PNI) change the intricate architecture, resulting in growth inhibition and loss of guidance over long distances. Neural tissue engineering aims to overcome limitations of cell-based therapeutics. Efforts are being made to create an optimal scaffold using natural, synthetic, and conductive polymers that match the biological, mechanical, and electrical properties of the native neural tissue. Combining biomaterials, cells, and biochemicals promotes axonal regrowth, facilitating functional recovery from neural nerve disorders. This review focuses on the recent advancements in neural tissue engineering technologies and their applications.